A reckless match - Bateman, Kate (St. Martin's Paperbacks, 2021)
Forced to retreat to his family's Welsh castle, Gryff Davies, the new Earl of Powys, is reunited with his childhood enemy Madeline Montgomery, who loathes him just as much as she ever did, until danger and meddling from their feuding families makes them realize that their animosity could be love.